2019
DOI: 10.1111/prd.12273
|View full text |Cite
|
Sign up to set email alerts
|

Viral, bacterial, and fungal infections of the oral mucosa: Types, incidence, predisposing factors, diagnostic algorithms, and management

Abstract: | Herpes simplex infections (human herpesvirus 1 and 2) | EpidemiologyChildren between 6 months and 3 years of age are at higher risk to exposure to herpes simplex virus type 1 through direct contact with How to cite this article: Bandara HMHN, Samaranayake LP. Viral, bacterial, and fungal infections of the oral mucosa: Types, incidence, predisposing factors, diagnostic algorithms, and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 325 publications
(304 reference statements)
1
17
0
Order By: Relevance
“…Previous studies have found that HAP is closely related to oral health [22,23]. Any in ammation or damage to the oral mucosa could promote bacterial adhesion, colonization, reproduction and infection [24,25]. Migration of this infection through the upper respiratory tract to the lower respiratory tract is common in clinical practice [6].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that HAP is closely related to oral health [22,23]. Any in ammation or damage to the oral mucosa could promote bacterial adhesion, colonization, reproduction and infection [24,25]. Migration of this infection through the upper respiratory tract to the lower respiratory tract is common in clinical practice [6].…”
Section: Discussionmentioning
confidence: 99%
“…History; clinical presentation; chest X-ray; cultures 36 Deep, irregular single painless ulcer with inverted margins and granulations on the floor with sloughing tissue associated with enlarged regional lymph node, tuberculomas, and nodules, commonly affecting the tongue 29,36 Indicated May manifests sore throat and development of palatal petechiae exudative pharyngitis, tonsillitis, and posterior cervical lymphadenopathy are common 35,36 Not indicated Supportive treatment, rest, and analgesics; Antiviral or corticosteroids treatment 36 Cytomegalovirus infection Serological test of CMVspecific antibodies or IgG; CMV-specific IgM antibodies 36 Persistent, solitary or numerous, painful or painless, shallow ulcerations, with a base covered by a yellow slough or pseudomembrane, and the margins can be rolled, elevated, with or without induration 36,37 Not indicated Antiviral drugs 36 Herpes simplex virus Clinical presentation; Virologic tests; Cytology smears stained with Giemsa or Papanicolaou stain; PCR; Serological tests 36 Blisters or vesicles with eruptions extremely painful and break in tiny, shallow-grey ulcers on a red base 29,36 Indicated Analgesics and antipyretics, topical anesthetics, and antiviral therapy 36 osteoblasts. [7][8][9][10] Based on Wilden and Karthein's research, 43 a relevant subject arises from the wavelength (energy range) between 600-700 nm; it is effective in triggering cell proliferation and differentiation.…”
Section: Tuberculosismentioning
confidence: 99%
“…Some may evade the natural defense barriers and both local and systemic nonimmune and immunological mechanisms and can be life threatening. Bandara and Samaranayake provide a comprehensive review of fungal, bacterial, and viral infections affecting the soft tissues of the mouth. This chapter provides epidemiology, risk factors, clinical presentation, diagnosis and treatment of common as well as relatively rare infections.…”
Section: Infections Of the Oral Mucosamentioning
confidence: 99%